الرؤية والأداة في شعر ابراهيم بن حسن الأسكوبي : دراسة وصفية تحليلية - زهراني، فيصل بن صالح (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This research examines the study of Ibrahim Al-askooby's poetry in his edited diwan (collection of poems) focusing on the importance of the poet and his era which was an era of transition in the Hijaz literature. The nature of this research necessitates dividing this thesis into a few chapters, in which the descriptive historical approach was used in the first chapter to trace the poet's life, identify the attributes of his era and how they had influenced his poetic vision have been identified. In the second chapter, the descriptive analytical approach has been used to investigate his vision of life by going through the subjects he addressed. The third chapter concentrates on his artistic poetry tools to highlight the strong and weak aspects of his poetic execution in which the criticism rules from his poetry were recognized. and the findings indicate the enquity of researchers to the poet and his literary era and the lack of attention from researchers to study his poetry in full comprehensive academic study even though because Al-askooby is one of the most prominent poets in Hijaz. The study showes that his poetic vision was affected by the social and political life events in his time and his distinguished literary character led his vision to the subjects he dealt with as well as his renovative role in it, where he had antecedence in its resurrection in the Hijaz environment.